Proportional influence of sea water and bicarbonate on the production of Spirulina sp. biomass with light-emitting diode lighting - Vasquez-Villalobos, Víctor (2014)
The study focused on the influence of the variables seawater proportion (%) and bicarbonate concentration on Spirulina sp. biomass production, using a Central Composite Rotational Design (CCRD) to evaluate the optimal regions of biomass production (ϕ), adaptation phase (λ), specific growth rate (µ) and generation time (G), using for each treatment the Gompertz mathematical model. The highest values of biomass (ϕ) log N/N0: 0.93 were obtained at 168.8 hours; in a culture medium with pH 8.8±0.1; at a temperature of 25°C; with salinity of 1.2% and 1.6 gL of bicarbonate. The lowest value of ϕ was 0.45±0.01; coincidentally obtained in repetitions of the central point, using a salinity of 0.7% and 3.0g/L of bicarbonate; in a medium with pH 9.1±0.4 to 25°C; which shows the importance of salinity provided by the volume of seawater relative to bicarbonate, in the production of Spirulina biomass. The lighting was 2.7±1.2 klx, provided by a White Light-Emitting Diode (WLED) during 12 continuous hours and an air injection of 0.86±0.09 L/s by a photo bioreactor with a 200 mL capacity. Only the values of ϕ, adjusted properly to the Response Surface with an R2 of 0.99 for a quadratic mathematical model and p < 0.05 with a 2.4% average absolute error.